Clinicopathological Features of Advanced Gastric Cancers which Were Misjudged and Subjected to Endoscopic Submucosal Dissection - Yorinari Ochiai; Daisuke Kikuchi; Naoko Inoshita; Junnosuke Hayasaka; Yugo Suzuki; Masami Tanaka; Kosuke Nomura; Hiroyuki Odagiri; Satoshi Yamashita; Akira Matsui; Toshiro Iizuka; Masanobu Kitagawa; et al. (Gastroenterology Research and Practice)
Background and Aims. Endoscopic submucosal dissection (ESD) is widely performed for early gastric cancer (EGC). We have sometimes encountered gastric cancer lesions for which ESD was performed and at which pathologically advanced cancer was found. In this study, we performed clinicopathological examination of lesions whose endoscopic diagnosis and pathology differed substantially. Methods. ESD was performed for 2,194 gastric cancer lesions (1,753 cases) in our institute from April 2005 through March 2015. The vertical margin was positive or status unknown in 51 lesions (2.3%); among these, muscularis propria (MP) or deeper infiltration was identified in 6 lesions from specimens obtained during subsequent surgery. In 1 lesion with MP invasion, the vertical margin was negative. We evaluated the clinicopathological features of these 7 lesions and retrospectively reviewed endoscopic indicators of submucosal invasion for EGC on white light imaging (WLI), narrow-band imaging magnifying endoscopy (NBI-ME), and endoscopic ultrasonography (EUS) performed previously. Results. Average age was 73.2±7.2 years, and all cases were men. The 7 lesions diagnosed as advanced cancer were 0.32% of 2,194 lesions and were all located in the U region (fundus). On retrospective review of endoscopic findings, 2 of 7 lesions on WBI, 3 of 6 lesions on NBI-ME, and 2 of 5 lesions on EUS met the criteria for indicating submucosal invasion of EGC. No lesions had findings on all 3 modalities. Conclusion. In rare cases, advanced gastric cancer could not be accurately diagnosed by endoscopy using various modalities. Each case had special characteristics making identification of deep infiltration difficult.